NANOSTRUCTURED ALLOYS AND MECHANICAL ALLOYING - L. Lu; M. O. Lai (Jurnal Sains Materi Indonesia, 2003)
NANOSTRUCTURED ALLOYS AND MECHANICAL ALLOYING. This paper reviews the formation of nanostructured alloys, recent development of nanocrystalline magnesium alloys and their nanocomposite synthesized via mechanical alloying. Though mechanical alloying was developed for the processing of oxide dispersion strengthening super-alloys, this technique offers the possibility of producing very fine crystallite size down to the nano-scale with flexibility in alloying so that the mechanical properties of the final composite can be tailored.